Morin Hydrate Inhibits TREM-1/TLR4-Mediated Inflammatory Response in Macrophages and Protects Against Carbon Tetrachloride-Induced Acute Liver Injury in Mice - Li, Xi; Yao, Qunyan; Huang, Jiying; Jin, Qianwen; Xu, Beili; Chen, Fangyuan; Tu, Chuantao (Frontiers in Pharmacology, 2019)
This study aims to investigate the protective effects of Morin hydrate (MH) against acute liver injury induced by carbon tetrachloride (CCl4) in mice and to elucidate the possible molecular mechanism of action. Mice were pretreated with MH (50 mg/kg body weight) or vehicle by oral gavage once daily for 5 days, followed by intraperitoneal injection of a single dose of CCl4 (1 mL/kg in olive oil). Mice were sacrificed 24 hours later; the blood and liver samples were harvested for analysis. We also examined the effects of MH on the inflammatory response in vitro model of lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages. Our results revealed that MH remarkably attenuated liver histopathological alterations, serum transaminases, hepatocyte death and inflammatory response induced by CCl4. Importantly, MH reduced expression of the triggering receptor expressed on myeloid cells-1 (TREM-1) and toll-like receptor 4 (TLR4) in vivo and in vitro. Moreover, MH dramatically inhibited IKBα degradation and subsequent nuclear factor-kB (NF-kB) p65 translocation into the nucleus and NF-kB-mediated cytokines such as tumor necrosis factor α (TNF-α), interleukin-1β (IL-1β) and IL-6. Additionally, MH also ameliorated CCl4-induced oxidative stress by enhancing the nuclear factor E2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1) expression in the injured livers. Taken together, MH has hepatoprotective activity and this effect may be elicited by attenuating macrophage-mediated inflammatory responses via inhibition TREM-1/TLR4/NF-kB signaling pathway and by regulating hepatic oxidative stress via enhancement Nrf2/HO-1 antioxidant pathway.